Post-2000 greening of Kalahari Desert and southern African grasslands reduces food and economic insecurity in Africa - Debashis Nath; Reshmita Nath; Wen Chen; Wenju Cai; Zizhen Dong; Ruowen Yang (Environmental Research Letters, 2025)
The Kalahari high-pressure system that forms the Kalahari and Namib Deserts of Southern Africa is maintained by the sinking motion of the Hadley circulation. Despite projected desertification under the climate change, beginning in the early 21st century the Kalahari Desert and grasslands of South Africa, Lesotho–Drakensberg highland and Eswatini has experienced a trend of greening/Savannisation. Here, we find that the disparity is likely due to strong multidecadal variability. A positive phase of the Atlantic multidecadal oscillation during this period has intensified the Hadley circulation and widened the Kalahari anticyclone, thereby facilitating moisture transport from the warm Angola–Benguela front to southern African landmasses. The advected moisture brought wetness at its periphery, which satisfied the water demand for cropland expansion (∼10%–15%) in southern Africa. A water-food-economy nexus is increasing Africa’s crop yields by approximately 25%, reducing food and economic insecurity through a nearly fourfold increase in agricultural exports and contributing approximately 26% to the continent’s total agricultural output. However, in the opposite phase of multidecadal variability, the superposition of greenhouse warming would exacerbate the drying trend that will amplify aridity.